Repeated Interactions and Improved Outcomes: An Empirical Analysis of Movie Production in the United States - Narayan, Vishal; Kadiyali, Vrinda (Management Science, 2016)
Many marketing activities take place within teams; these team activities often involve repeated interactions among team members over several projects. We study whether and what types of repeated interactions improve current production success, and under what conditions. We use a unique data set of past experience, successes, and pairwise interactions between members of production teams of 1,123 movies and employ dynamic panel data estimation methods. Three unique insights emerge. Interactions between the producer and other team members have a greater effect on revenues than other repeated pairs for which consumers might have preferences. In many instances, repeated interactions with current team members are more revenue enhancing than individual successes in past movies. In fact, repeated interactions between team members improve current revenues even if such interactions were unsuccessful. We discuss theoretical explanations for these results and the managerial implications for successful team formation in movie production. Data, as supplemental material, are available at http://dx.doi.org/10.1287/mnsc.2014.2139 . This paper was accepted by J. Miguel Villas-Boas, marketing.